2009
DOI: 10.1017/s0003598x00099373
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Columbian geometric earthworks in the upper Purús: a complex society in western Amazonia

Abstract: It's an ill wind that blows nobody any good. The combination of land cleared of its rainforest for grazing and satellite survey have revealed a sophisticated pre-Columbian monument-building society in the upper Amazon Basin on the east side of the Andes. This hitherto unknown people constructed earthworks of precise geometric plan connected by straight orthogonal roads. Introducing us to this new civilisation, the authors show that the ‘geoglyph culture’ stretches over a region more than 250km across, and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 16 publications
1
99
0
9
Order By: Relevance
“…Excavations of the geoglyphs have shown that they were built and used sporadically as ceremonial and public gathering sites between 2000 and 650 calibrated years before present (BP), but that some may have been constructed as early as 3500-3000 BP (28)(29)(30). Evidence for their ceremonial function is based on an almost complete absence of cultural material found within the enclosed areas, which suggests they were kept ritually "clean," alongside their highly formalized architectural forms (mainly circles and squares)-features that distinguish the geoglyphs from similar ditched enclosures in northeast Bolivia (5,31).…”
mentioning
confidence: 99%
“…Excavations of the geoglyphs have shown that they were built and used sporadically as ceremonial and public gathering sites between 2000 and 650 calibrated years before present (BP), but that some may have been constructed as early as 3500-3000 BP (28)(29)(30). Evidence for their ceremonial function is based on an almost complete absence of cultural material found within the enclosed areas, which suggests they were kept ritually "clean," alongside their highly formalized architectural forms (mainly circles and squares)-features that distinguish the geoglyphs from similar ditched enclosures in northeast Bolivia (5,31).…”
mentioning
confidence: 99%
“…Los cacicazgos y civilizaciones densamente pobladas de la Amazonía, sociedades con una organización regional y cultural definida, que tuvieron su apogeo hacia el año 1200 (AD), fueron extintas de forma violenta por enfermedades exóticas (Clement, 1999) y la influencia de las culturas europeas (Roosevelt, 1993;Pärssinen et al, 2009). Mediante estimaciones basadas en la presencia de tierras negras amazónicas, producto de la manipulación agroecológica del humano, Clement (2015) sugiere un estimado de entre 8 a 10 millones de habitantes amazónicos antes de la llegada de los europeos, población que fue reducida hasta en un 80% después de la fiebres del caucho y el oro en la época republicana de las naciones suramericanas.…”
Section: Poblaciones Y Culturas Colonizadasunclassified
“…A partir do ano de 2007, as pesquisas no Acre intensificaram-se consideravelmente. Tanto os projetos acadêmicos de pesquisa (PÄRSSINEN et al , 2009SAUNALUOMA, 2012;SCHAAN et al 2007SCHAAN et al , 2012, como os trabalhos de arqueologia de contrato (por exemplo, SCHAAN & BUENO, 2008a, 2008bSCHAAN & SAUNALUOMA, 2010) tem aumentado nosso conhecimento sobre a arqueologia regional. No entanto, para desenvolver um entendimento compreensivo do Acre pré-colombiano, muitos temas ainda precisam ser estudados.…”
Section: História Das Pesquisas Arqueológicasunclassified